1992
DOI: 10.1007/bf00161246
|View full text |Cite
|
Sign up to set email alerts
|

The current management of herpetic eye disease

Abstract: Herpes simplex disciform keratitis is a difficult condition. The general feeling is that it is an immune disease, mediated by the virus, possibly located in the endothelial cells. It is frequently combined with inflammation in the trabecular meshwork and with uveitis. There is some controversy in relation to treatment and it has been suggested that anti-virals will control herpetic disciform keratitis, particularly if the patient has never had steroids previously. The authors of this paper have, in the past, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Endothelial disease typically presents independently of other forms of HSV keratitis and only few studies are available to guide treatment . These compare topical betamethasone with topical acyclovir against topical acyclovir alone (all five times a day) and found that the addition of steroid resulted in a faster response and fewer treatment failures than antiviral alone.…”
Section: Uses Of Locally Administered Steroidsmentioning
confidence: 99%
“…Endothelial disease typically presents independently of other forms of HSV keratitis and only few studies are available to guide treatment . These compare topical betamethasone with topical acyclovir against topical acyclovir alone (all five times a day) and found that the addition of steroid resulted in a faster response and fewer treatment failures than antiviral alone.…”
Section: Uses Of Locally Administered Steroidsmentioning
confidence: 99%
“…This can be a problem particularly in patients with tear film disease. 20 Acyclovir, taken in oral form, has also been shown to be effective in the treatment ofherpes simplex keratitis.21…”
mentioning
confidence: 99%
“…The blended polymer fibers achieved a release that is desirable for treating endothelial keratitis. [ 33 ] The faster drug release of the polymer fibers comprising Tween 80 can be attributed to improved water penetration into deeper fiber layers and accelerated fiber degradation. Furthermore, the complete matrix degradation of the fiber mats occurred over a period of 6–8 weeks (data not shown), which is in good accordance with the literature.…”
Section: Resultsmentioning
confidence: 99%